Economic Sanctions and Russia’s Financial System - Igor N. Molchanov (Финансы: теория и практика, 2017)
Topic. The problem of functioning of the financial system in the face of uncertainty is complicated by the entered by Western countries anti-Russian economic sanctions. We discussed the peculiarities of functioning of the financial system in a “new normality” from the point of view of systemic and institutional approaches. We analyse sources of financial resources and financial instruments, the practical application of which allows overcoming the negative effects from the introduction of anti-Russian economic sanctions.Purpose. Author’s study of the national financial system under conditions of new economic reality and the existing approaches to its build up. Grounding the benefits of forming the structure of the financial system using the sectoral approach based on the methodology of the national accounts system.Methodology. The study is based on the dialectical method. In the study were applied the system and institutional approaches, analytical, expert and statistical methods.Results. The passivity of the financial institutions, nonfinancial organizations and population complicates the development of financial relations of economic agents. Russia’s financial system as a whole and its structural elements are experiencing a shortage of financial resources, which hampers the functioning of the national economy and the fulfillment of national obligations. Actualization of tasks of financial policy and the adoption of non-standard management decisions should be aimed at mobilizing financial resources and upgrading the stability of the financial system.Conclusions. Despite the difficult economic situation, it is necessary to rebuild the financial system of Russia based on the needs of innovation-oriented market economy, in the direction of overcoming the consequences associated with the introduction of anti-Russian economic sanctions. Strategic vectors for increasing the financial resources should be investment in innovations and creation of new technological order. A balanced financial policy, efficient management and coordination of all stakeholders will contribute to improving institutions’ performance of the national financial system and meeting the needs in the financial resources of all economic agents.